Removal of zinc (II) in water using chitosan - graphene oxide composite - Lina, Andrew V.
Zinc is among the heavy metals which causes environmental problems mainly in terms of water contamination. This study was undertaken to offer supplemental and potential solution to this issue. Its main objective was to find out the effectiveness of a composite material, consisting of chitosan and graphene oxide while employ1ng the process of adsorption in the removal of zinc in aqueous solution. Specific object1ves included the determination of the result of varying concentration ratios of chitosan and graphene oxide, investigating the effects of adsorption operation parameters such as initial pH, temperature, and adsorption dosage, conducting isotherm and kinetic studies and the characterization of the individual surface characteristics of graphene oxide and chitosan. This study was performed through the preparation of zinc solutions, synthesis of graphene oxide, preparation of the chitosan-graphene oxide composite adsorbents and the carrying out of adsorption experiments. Initially, varying ratios of chitosan and graphene oxide (CS-GO) were investigated. Among the ratios, pure GO (0:100) had the highest adsorption with 50.10% of zinc removed. It was noted that the higher the content of GO, the better was the adsorption. For this reason, the 10:90 ratio was utilized further in the study. For the effect of varying initial pH, it was observed that the adsorption was strongly dependent on pH, with 80.34% removal at pH 11. Varying temperature had revealed that the adsorption progresses with the increasing temperature. The adsorption capacity was 50.70 mg/g at the highest considered temperature of 40 °C. Regarding the effects of varying dosage, it was found out that increasing the amount of adsorbent lowers the amount of zinc removed. Higher % removal was acquired with the increasing adsorbent dosage Isotherm study showed that the adsorption fitted well with the Langmuir isotherm model. Kinetics study revealed that the said process conformed with the pseudo-second-order model. Characterization using FTIR and SEM strengthened the reliance of the amount of zinc removed with the amount of GO in the CS-GO composite. Generally, it was observed that CS-GO adsorbs zinc ions in water and its effectiveness were affected by the above factors and parameters.